A Use-Based Measure of Accessibility to Linear Features to Predict Urban Trail Use - John R. Ottensmann; Greg Lindsey (Journal of Transport and Land Use)
The standard Hansen measure of accessibility is extended to provide a use-based measure of accessibility reflecting the elasticity of use with respect to the level of provision of facilities. This is further extended to provide a measure of accessibility to linear features, such as trails (as opposed to features at point locations such as parks and libraries). Results from a survey on the use of urban trails in Indianapolis, Indiana are used to test the ability of this accessibility measure to predict trail use. The use-based measure of accessibility to linear features provides better predictions of use and more consistent estimates of the effects of distance and level of facility provision on trail use.